1997
DOI: 10.1109/3468.553230
|View full text |Cite
|
Sign up to set email alerts
|

Discrimination gain to optimize detection and classification

Abstract: A method for managing agile sensors to optimize detection and classication based on discrimination gain is presented. Expected discrimination gain is used to determine threshold settings and search order for a collection of discrete detection cells. This is applied in a low signal-tonoise environment where target-containing cells must be sampled many times before a target can be detected or classied with high condence. The goal of sensor management i s i n terpreted to be to direct sensors to optimize the prob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
68
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(68 citation statements)
references
References 6 publications
0
68
0
Order By: Relevance
“…The main assumption is that the observer can use features which allow to discriminate between the different affordances and the effector. This approach is similar to that of [8] and [18] but, instead of being limited to track or to find objects in a dynamic environment, it allows for the active recognition of a dynamic event.…”
Section: Action Recognition With Dynamic Allocation Of Attentionmentioning
confidence: 99%
“…The main assumption is that the observer can use features which allow to discriminate between the different affordances and the effector. This approach is similar to that of [8] and [18] but, instead of being limited to track or to find objects in a dynamic environment, it allows for the active recognition of a dynamic event.…”
Section: Action Recognition With Dynamic Allocation Of Attentionmentioning
confidence: 99%
“…Several informationtheoretic functions have been proposed for this purpose. Cross entropy was used in [28] to solve a multisensor-multitarget assignment problem, and in [29,30] to manage agile sensors with Gaussian models for target detection and classification. Entropy and the Mahalanobis distance measure were used in [27] for sensor selection in ad-hoc sensor networks.…”
Section: Measurement Information Valuementioning
confidence: 99%
“…While robot path planning typically aims to optimize a deterministic additive function such as Eucledian distance, sensor planning aims to optimize a stochastic sensing objective that is not necessarily additive. Another basic difficulty in sensor planning is that, although the measurements ultimately determine the sensor performance, they cannot be factored into the planning problem because the sensor's position must be planned prior to obtaining the sensor's measurements [27][28][29][30][31]. Recently, several authors have shown that this difficulty can be overcome by an approach known as information-driven sensor planning, which uses information theoretic functions to estimate the measurements' value prior to deploying the sensor [27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…Most of the literature is in the area of managing sensors to maximize kinematic information gain only [1][2]. Some prior art exists in managing sensors for maximizing ID and search as well [3][4]. One can use information theoretic criteria such as entropy, discrimination information, mutual information, etc.…”
mentioning
confidence: 99%
“…Hintz and McVey [45] used entropy for search, track and ID tasks. Work in [46][47][48][49][50][51][52][53] use information measures such as entropy and discrimination gain for goals such as determining resolution level of a sensor, determining priority of search and track tasks, etc. Hintz et al [9,10] use the Shannon entropy, as we do in this paper, while Schmaedeke and Kastella [11] have chosen to use Kullback-Leibler (KL) divergence as measure of information gain.…”
mentioning
confidence: 99%